Intentional re-implantation in a left mandibular second molar with broken file in apical third of mesiobuccal root: a case report - Hajrah Tariq; Mehak Baber Ali; Zarnab Rizwan; Rizwan, Ghina; Sidra Leghari; Alia Ahmed (Journal of the Pakistan Medical Association, 2022)
Intentional re-implantation is done in cases of endodontic failures where conventional treatment options either fail or cannot be carried out due to any reason. It involves extraction of the offending tooth, extra oral apicectomy, followed by reinsertion of the tooth into its anatomical location. The following case report presents a situation where an endodontic instrument was separated in the mesiobuccal root of the left mandibular second molar during instrumentation that could not be retrieved. The decision of intentional re-implantation was made after detailed discussion with the patient, weighing pros and cons of each available treatment option. Fortunately, a favourable outcome was observed over a span of one year and the patient is still on follow-up for evaluation of long-term prognosis. Key Words: Intentional re-implantation, Apicectomy, Broken file.